2020
DOI: 10.1016/j.intimp.2020.106578
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic acid alleviates hepatic inflammation injury in viral hepatitis disease via a HMGB1-TLR4 signaling pathway

Abstract: Various human disorders are cured by the use of licorice, a key ingredient of herbal remedies. Glycyrrhizic acid (GL), a triterpenoid glycoside, is the aqueous extract from licorice root. Glycyrrhetinic acid (GA) has been reported to be a major bioactive hydrolysis product of GL and has been regarded as an anti-inflammatory agent for the treatment of a variety of inflammatory diseases, including hepatitis. However, the mechanism by which GA inhibits viral hepatic inflammatory injury is not completely understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Pyroptotic macrophage death may accelerate undesirable immune hyperactivity and immunosuppression, which is a potential mechanism associated with late mortality from sepsis [8]. In hepatic infectious disease, the release and activity of HMGB1 as a cytokine could be suppressed by glycyrrhizinic acid (GA) [9]. By binding with TLR4, HMGB1 regulates the hepatitis viruses-induced immunological axis, providing a new therapy strategy for the treatment of acute viral hepatitis in the clinical practice [10].…”
Section: Hmgb1 In Inflammationmentioning
confidence: 99%
“…Pyroptotic macrophage death may accelerate undesirable immune hyperactivity and immunosuppression, which is a potential mechanism associated with late mortality from sepsis [8]. In hepatic infectious disease, the release and activity of HMGB1 as a cytokine could be suppressed by glycyrrhizinic acid (GA) [9]. By binding with TLR4, HMGB1 regulates the hepatitis viruses-induced immunological axis, providing a new therapy strategy for the treatment of acute viral hepatitis in the clinical practice [10].…”
Section: Hmgb1 In Inflammationmentioning
confidence: 99%
“…TLRs are capable of modulating several immune responses, especially during the infectious process [ 128 ]. Several studies have shown that the secretion of TLR-3, TLR-4, TLR-7, TLR-9, and TLR-10 genes from hepatic tissue was upregulated in some viral infection models [ 129 , 130 ], and GA or GL is capable of inhibiting these receptors ( Table 1 ) [ 131 134 ]. It was established that the TLR-4 pathway comprises of two dissimilar signaling pathways such as the myeloid differentiating primary response gene 88- (MyD88-) dependent as well as the MyD88-independent pathway [ 135 , 136 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…A study revealed that TLR-4 was the fundamental receptor of the innate immune signaling responses to influenza virus as well as other respiratory viruses [ 137 ]. Several studies have shown that the TLR-4 was more associated with respiratory syncytial virus and human papillomavirus infections [ 129 , 138 , 139 ]. Shi et al revealed that TLR-4 gene deficiency was not associated with the downregulation of virus titer in the liver during MHV-A59 infection [ 129 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 2 more Smart Citations